Competitive antagonistic action of laccase between Trichoderma species and the newly identified wood pathogenic Ganoderma camelum - Umar, Aisha; Elshikh, Mohamed S.; Aljowaie, Reem M.; Hussein, Juma Mahmud; Dufossé, Laurent; Wu, Chenghong; Lu, Junxing (Frontiers in Microbiology, 2024)
Ganoderma, a well-known genus in the Ganodermataceae family, has caused the extinction of several tree species due to its pathogenicity. This study explored the pathogenic effect of a newly identified Ganoderma species on trees and its competitive efficiency against Trichoderma species. Ganoderma camelum sp. nov. is characterized by small sessile basidiomata and a velvety, soft, camel-brown pileus. Phylogenetic analysis and ITS rDNA sequences indicated that the species were Trichoderma and Ganoderma camelum. Both fungal species competed antagonistically by secreting laccase. The laccase activity of G. camelum, with a value of 8.3 ± 4.0 U/mL, demonstrated the highest competitive activity against Trichoderma species. The laccase produced by T. atroviride (2.62 U/mL) was most effective in countering the pathogenic action of the novel G. camelum. The molecular weights of laccase were determined using SDS-PAGE (62.0 kDa for G. camelum and 57.0 kDa for T. atroviride). Due to the white rot induced by this Ganoderma species in the host tree, G. camelum showed the highest percentage inhibition of radial growth (76.3%) compared to T. atroviride (28.7%). This study aimed to evaluate the competitive antagonistic activity of Ganoderma and Trichoderma on malt extract agar media in the context of white rot disease in the host tree. This study concluded that the laccase from G. camelum caused weight loss in rubber wood blocks through laccase action, indicating tissue injury in the host species. Therefore, it was also concluded that G. camelum was more effective in pathogenic action of the host and resisted the biological action of T. atroviride. In principal components analysis (PCA), all the species associated with laccase exhibited a very strong influence on the variability of the system. The PIRG rate (percentage inhibition of radial growth) was strongly and positively correlated with laccase activity.